Application of the Design Thinking method in the area of software requirements - Huarcaya Zapana, Gerson Italo (2021)
This article presents the application of Design Thinking in the area of software requirements to help and solve some problems that exist in software development. It is intended to integrate the tools, features and phases of Design Thinking into the activities of the analysis of software requirements. The main objective is to integrate the Design Thinking approach in a way that helps in the software requirements and finally see and analyze the results obtained .